Correlation Between HbA1c Levels and Chronic Complications in Patients with Type 2 Diabetes Mellitus at UNS Hospital - Probowirasmi, Prasasti; Sukmagautama, Coana; Munawaroh, Siti (Faculty of Medicine Universitas Sebelas Maret, 2025)
Introduction: Diabetes mellitus has been a burden for global health with 422 million patients. Complication in diabetes patients increase the cost of patient care. This research was conducted to determine the correlation between HbA1c levels and chronic complications of type 2 diabetes mellitus in UNS hospital. Furthermore, the HbA1c predictive threshold and the incidence of chronic problems linked to type 2 diabetes mellitus are also explained in this paper.Methods: This study used a retrospective cross-sectional design based on 133 inpatient medical records from 2022. Data were collected using a purposive sampling method that adjust the inclusion and exclusion criteria. Data analysis using SPSS 23 software with logistic regression.Results: (1) There is a significant correlation of HbA1c levels and chronic complication of type 2 diabetes mellitus patients in UNS Hospital. (2) HbA1c score of 6.5% or above is best cutoff to use for determining whether type 2 diabetes mellitus was developing chronic problems. (3) The prevalence of the organ with the most involvement in complication is cardiovascular (51,4%).Conclusion: There is a significant correlation of HbA1c levels and chronic complication of type 2 diabetes mellitus in UNS Hospital with cardiovascular as the organ with the most involvement.